Agency Evidentialism: Trust and Doxastic Voluntarism - Snježana Prijić-Samaržija (Rivista di Estetica, 2018)
In debates about trust and testimony, epistemologists have traditionally been divided into two groups: those who hold that accepting the testimony of other people should be a kind of credulity without evidence (anti-reductivism) and those who assert that we shouldn't recognize any testimony as true or justified without appropriate evidence (reductivism). I will argue in favour of the evidentialist position about trust, or the stance that epistemically responsible trust is a matter of evidence, but also in favour of the thesis that the position assumed by anti-reductivists is not necessarily an anti-evidentialist position. The crucial difference between anti-reductivism and reductivism does not pertain to the question of evidence, but to epistemic agency. Finally, I will argue against anti-reductivism and in favour of agency evidentialism, wherein it is assumed that accepting testimony is a kind of agency where our (reflective) control is strong enough to ensure that our trust is responsible. The version of agency evidentialism which I here support presumes: (i) doxastic voluntarism, or the existence of intellectual freedom in the sense that we have to be capable of certain intellectual choices or decisions, and (ii) virtue epistemology, or the normative approach according to which the target of epistemic evaluation is an epistemic agent to whom we ascribe epistemic or intellectual virtues or vices (epistemic responsibility, epistemic conscientiousness or like.)